2021
DOI: 10.1021/acsami.1c08833
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Removal of Neonicotinoid Insecticides by Thioether-Based (Multivariate) Metal–Organic Frameworks

Abstract: Circumventing the impact of agrochemicals on aquatic environments has become a necessity for health and ecological reasons. Herein, we report the use of a family of five eco-friendly water-stable isoreticular metal–organic frameworks (MOFs), prepared from amino acids, as adsorbents for the removal of neonicotinoid insecticides (thiamethoxam, clothianidin, imidacloprid, acetamiprid, and thiacloprid) from water. Among them, the three MOFs containing thioether-based residues show remarkable removal efficiency. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 71 publications
(119 reference statements)
1
39
0
Order By: Relevance
“…The gram-scale preparation of 1 follows a previously reported experimental procedure (see Experimental Section in Supporting Information). 50 The experimental PXRD pattern of 1 is identical to the calculated one ( Figure S2 ), which confirms the homogeneity of the bulk sample and its isostructurality to the single-crystals selected for SCXRD (see below). As a preliminary step to the preparation of MTV-MOF/SWCNT-BP , we evaluated the behavior of MTV-MOF 1 in the removal of Pb 2+ from water (see the Supporting Information for details on preparation of 1 ).…”
Section: Resultssupporting
confidence: 77%
“…The gram-scale preparation of 1 follows a previously reported experimental procedure (see Experimental Section in Supporting Information). 50 The experimental PXRD pattern of 1 is identical to the calculated one ( Figure S2 ), which confirms the homogeneity of the bulk sample and its isostructurality to the single-crystals selected for SCXRD (see below). As a preliminary step to the preparation of MTV-MOF/SWCNT-BP , we evaluated the behavior of MTV-MOF 1 in the removal of Pb 2+ from water (see the Supporting Information for details on preparation of 1 ).…”
Section: Resultssupporting
confidence: 77%
“…In contrast, AC was able to obtain significantly lower adsorption efficiencies ranging from 5 to 48% for the same neonics [ 25 ]. Negro et al [ 26 ] showed the ability of MOFs to adsorb acetamiprid and thiacloprid from aqueous solutions of 100 mg L −1 , in less than 30 s. The achieved removal efficiencies were 60% and 30% for imidacloprid and thiamethoxam, respectively, and the q max for all the pesticides in the study ranged from 400 and 500 mg g −1 . Ma et al [ 27 ] used potassium hydroxide activated magnetic microporous loofah sponge biochar to remove imidacloprid, registering a maximum adsorption capacity of 738 mg g −1 , whereas when a potassium hydroxide activated magnetic microporous sugarcane bagasse biochar was used as adsorbent for the same insecticide, a lower maximum adsorption capacity of 313 mg g −1 was achieved [ 28 ].…”
Section: Resultsmentioning
confidence: 78%
“…Several materials have been reported in the literature as adsorbents for a variety of insecticides, for instance, porous AC [ 19 ], granular AC [ 21 ], a combination of AC and florisil [ 22 ], DMPIS [ 23 ], chitin-derived three-dimensional nanomaterials [ 24 ], MOFs [ 26 ], POCIS [ 25 ], potassium hydroxide activated magnetic microporous loofah sponge biochar [ 27 ], and potassium hydroxide activated magnetic sugarcane bagasse biochar [ 28 ]. Mohammad et al [ 19 ] studied the application of micro- and mesoporous activated carbon (TPAC) to remove acetamiprid, in which a maximum adsorption capacity of 35.7 mg g −1 was achieved at the equilibrium time of 240 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of the adsorption of relatively large molecules (drugs, cosmetics, pesticides, etc.) from liquids for applications in drug delivery, pollutants removal, or analytical chemistry, there are fewer studies dedicated to the analysis of the adsorption processes and the mechanisms involved. ,,, Considering that these applications benefit from the adsorption of large amounts of target molecules from liquids, they all should share in a comprehensive manner the efforts in the analysis of adsorption of target molecules by MOFs. Essentially because these target molecules are frequently the same, they are sometimes delivered as drugs to the organism, they need to be removed from water for being pollutants, or it is important to monitor their concentration in water, food, and/or biological samples.…”
Section: Introductionmentioning
confidence: 99%